Racial/ethnic differences in the prevalence of internalizing symptoms: Do Latin-American immigrant show more symptomatology than Spanish native-born adolescents?. (March 2014) - Romero-Acosta, Kelly; Penelo, Eva; Noorian, Zahra; Ferreira, Estrella; Domènech-Llaberia, Edelmira
This study mainly compared the prevalence of internalizing symptoms of 834 Spanish and 159 Latin-American immigrant adolescents. Participants completed self-report measures about depression, anxiety and somatic symptoms and a socio-demographic questionnaire. The results indicated that being Latin-American was associated with higher levels of depressive symptoms and being female was related to higher depressive and anxiety symptoms. Gender differences were more prevalent in Spaniards than in Latinos, with girls showing more symptoms than boys. High socio-economic status was negatively related to depressive symptoms and anxiety. The results may alert clinicians of the importance of assessing depressive symptoms in Latino adolescents in order to treat this group of youths effectively.